The Impact of FTA on Trade Volume and Terms of Trade between Pakistan and China. (August 2022) - Ahmed, Arsalan; Rahman, Inam Ur; Jauhari, Samana
The primary purpose of this study is to examine the impact of free trade agreements on trade volume and terms of trade between Pakistan and China. It examines the effect of the Pakistan–China Free Trade Agreement (PCFTA) on sector-wise trade welfare for both countries. Using the model of Lloyd and Maclaren, this study has quantified the trade welfare effect for both countries through trade volume, intra-union terms of trade and extra-union terms of trade in the context of PCFTA. The study concludes that the trade welfare increases for China and decreases for Pakistan after the complete execution of PCFTA. Also, there has been a trade creation for China and trade diversion for Pakistan by the PCFTA. JEL Codes: F15, F10, F13, I30, F60, F02